Managing an Electricity Shortfall : A Guide for Policy Makers - World Bank (World Bank, 2012)
Economic growth in Central America has increased rapidly over the past 20 years. Currently, the gross domestic product (GDP) per capita for the six Central American countries of Costa Rica, El Salvador, Guatemala, Honduras, Nicaragua and Panama averages approximately US$3,600. However, masked behind this average figure is a Sub region of 40 million people with a wide variety of income, where more than half of the population lives in poverty. Energy in general and electricity specifically are critical for economic development. Electricity is needed to power the machinery that supports income-generating opportunities. Capital (both domestic and foreign) is attracted to countries that are able to offer an affordable, reliable source of electricity for businesses. Although the individual electricity markets of Costa Rica, El Salvador, Guatemala, Honduras, Nicaragua and Panama are not large, together the six countries collectively generated nearly 38 Terawatt-hours (TWh) of power, equivalent to around 70 percent of the annual electricity supply of a medium-sized country in Latin America. The World Bank has undertaken a series of studies to better understand the energy challenges facing these six Central American countries that are to be joined by Sistema de Interconexion Electrica para America Central (SIEPAC) and to identify actions to promote the sound development of the sector. These studies have been prepared by a team of policy experts, engineers and economists as part of an integrated series entitled the Central America programmatic energy studies, with a primary focus on the electricity subsector. The initial phase of this programmatic series includes three modules. The first module is general issues and options; second module is managing an electricity shortfall; and the third module is structure and regulatory challenges. This particular document, the managing an electricity shortfall module, provides a framework for action and a broad menu of options available to policy makers to bridge a supply-demand gap in the short- to medium-term.